Anatoly C2011, new variety of durum wheat for sowing in El Bajío and northern Mexico - Solís Moya Ernesto; Huerta Espino, Julio; Villaseñor Mir Héctor Eduardo; Perez Herrera, Patricia; de la Cruz González María de Lourdes (Revista Mexicana de Ciencias Agrícolas, 2018)
Recent efforts in El Bajío Experiment Station of the National Research Institute for Forestry, Agriculture and Livestock (INIFAP-Mexico) have allowed the development of wheat varieties of high performance and high levels of disease resistance.Amongthesesuperiorgenotypesisthenewvariety Anatoly C2011, which produces 10% higher yield than Gema C2004 besides, it is resistant to stripe rust, moderately resistant to leaf rust and has similar quality. Anatoly C2011 seeds are available in El Bajío, INIFAP ́s experimental station.